Evolution of access network sharing towards software based passive optical network: can virtual OLTs run at full line rate? - Ruffini, Marco (My University, 2020)
This paper summarises how access network sharing has evolved from physical layer unbundling to fully virtualised architectures. We address one of the crucial question in access network virtualisation: whether fully virtualised PONs can run at line rate over general purpose processing units. This paper provides an experimental insight into this query, showing that it is possible to run XGS-PON at line rate, if additional hardware acceleration is provided, e.g., for cryptographic functions.
Optical Network Design and Modeling conference (ONDM)
PUBLISHED
Keywords: DBA; Virtualization; Passive Optical Network (PON); NFV; SDN; Access